2018
DOI: 10.1088/1361-6528/aadd6e
|View full text |Cite
|
Sign up to set email alerts
|

3D N-doped carbon framework with embedded CoS nanoparticles as highly active and durable oxygen reduction and evolution electrocatalyst

Abstract: Development of bifunctional non-metal electrocatalyst for oxygen reduction reactions (ORRs) and oxygen evolution reactions (OERs) with high efficiency, durable stability and low cost is a crucial and challenging issue. However, the heteroatom-doped carbon material including a carbon-based conductive additive would be easily oxidized under the high potential needed for driving the OER. Besides, the interaction between the heteroatom-doped carbon material that possesses electrocatalyst activity and a carbon-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It is known that Fe is the only common metal element in all biological nitrogenases in nature. As a cheap transition-metal element, Fe compounds can inject electrons from the occupied d orbital into the unoccupied empty orbital in N 2 to promote the d–2π* coupling between Fe and the absorbed N 2 molecule. The empty d orbitals in Fe can also accommodate electrons to form diverse compounds, making Fe-based catalysts highly efficient and low-cost electrocatalysts for N 2 fixation. Previous studies have reported that Fe-based sulfides can effectively catalyze nitrogen fixation as an electron-transfer carrier for N 2 reduction. However, the poor electrical conductivity and the low electrochemically active surface area (ECSA) of the reported Fe-based sulfides lead to low Faraday efficiency (FE) and yield rate of NRR. Hence, it is challenging and critical to purposefully develop an active and durable Fe-based catalyst for N 2 fixation. It has been proved that element doping engineering can not only improve the electronic structure of the catalysts but also introduce extra defects to further improve the catalytic activity. , Co element doping into Fe-based nanomaterials can be an effective way to reasonably modulate the electronic structure of the catalyst due to the smaller atom size and larger electronegativity of the Co atom, as well as the d–d coupling to reduce the free-energy barrier of dissociating the NN triple bond, which has not been explored before.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that Fe is the only common metal element in all biological nitrogenases in nature. As a cheap transition-metal element, Fe compounds can inject electrons from the occupied d orbital into the unoccupied empty orbital in N 2 to promote the d–2π* coupling between Fe and the absorbed N 2 molecule. The empty d orbitals in Fe can also accommodate electrons to form diverse compounds, making Fe-based catalysts highly efficient and low-cost electrocatalysts for N 2 fixation. Previous studies have reported that Fe-based sulfides can effectively catalyze nitrogen fixation as an electron-transfer carrier for N 2 reduction. However, the poor electrical conductivity and the low electrochemically active surface area (ECSA) of the reported Fe-based sulfides lead to low Faraday efficiency (FE) and yield rate of NRR. Hence, it is challenging and critical to purposefully develop an active and durable Fe-based catalyst for N 2 fixation. It has been proved that element doping engineering can not only improve the electronic structure of the catalysts but also introduce extra defects to further improve the catalytic activity. , Co element doping into Fe-based nanomaterials can be an effective way to reasonably modulate the electronic structure of the catalyst due to the smaller atom size and larger electronegativity of the Co atom, as well as the d–d coupling to reduce the free-energy barrier of dissociating the NN triple bond, which has not been explored before.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Among various types of exible devices, ber-based structures are highly desirable for wearable electronics due to their light-weight, excellent stability, exible nature and comfort. [6][7][8][9][10][11][12][13][14][15] Despite the fact that various designs for smaller, thinner and lighter Li-ion batteries (LIBs) have been developed in recent years, the existing battery technology is far from the practical exible applications. Meanwhile, a linear and omnidirectional exhibition of wire-type batteries has been carried out without traditional restrictions, allowing various product designs.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectrum was measured to further affirm the composition and hybrid structure in Figure f. Raman spectra show that the characteristic peaks of CoS at 338.0, 403.2, and 690.6 cm –1 arise in CoS/PNCFs and MnS–CoS/PNCFs, indicating the existence of CoS . It is not difficult to discover that there is a relative weaker peak at 656.3 cm –1 for MnS–CoS/PNCFs can be ascribed to be MnS species .…”
Section: Resultsmentioning
confidence: 96%
“…53,54 The Raman spectrum was measured to further affirm the composition and hybrid structure in Figure 2f. Raman spectra show that the characteristic peaks of CoS at 338.0, 403.2, and 690.6 cm −1 arise in CoS/PNCFs and MnS−CoS/PNCFs, indicating the existence of CoS. 55 It is not difficult to discover that there is a relative weaker peak at 656.3 cm −1 for MnS− CoS/PNCFs can be ascribed to be MnS species. 56 Moreover, two characteristic peaks centered at 1332.8 cm −1 (D-band) and 1591.9 cm −1 (G-band) are observed of MnS−CoS/PNCFs, and the corresponding I D /I G value is 1.03, while the CoS/ PNCFs is 1.01.…”
Section: Resultsmentioning
confidence: 99%